Morphology and genetic variations of Aethalops (Chiroptera: Pteropodidae) using mitochondrial and nuclear genes - Roberta Chaya Tawie, Tingga (Universiti Malaysia Sarawak, (UNIMAS), 2010)
t Aethalops is a mountain endemic fruit bat which consists of two species, namely, Aethalops aequalis and A. alecto. A. aequalis is endemic in Borneo only whereas A. alecto can be found on islands in Indonesia and also in Peninsular Malaysia. A. aequalis was previously classified as subspecies to A. alecto however, most recent study on Aethalops suggested A. aequalis as a single unit species distinctly different from A. alecto. Two approaches used in this study which were molecular and morphometric techniques. The objectives of this study were to clarify the current taxonomic status of A. aequalis and its phylogenetic relationship with A. alecto. Populations of A. aequalis in Sabah and Sarawak were investigated to detect any genetic variation between the geographic groups and among populations. This study also aimed to determine any morphological variation among the populations and to investigate if morphological variations correlate with molecular genetic distant. The fourth aim of this study was to provide as many data or information that could assist in the conservation management of Aethalops in Borneo specifically as this species is endemic mountain bat. Individuals in this study were sampled from seven populations in Sabah and Sarawak. Altogether, there were 70 individuals obtained from fresh samples and voucher specimens. They were categorised into three groups, namely, Southwest Sarawak (Mount [Mt] Penrissen and Mt Pueh), Northeast Sarawak (Mt Murud, Mt Mulu and Bario) and Sabah (Mt Kinabalu and Mt Trus Madi). For morphometric analysis, 65 skulls of adult A. aequalis were extracted with 22 cranial and dental characters measured and recorded. Mitochondrial ( COI) and nuclear (Rag2) DNA genes were used in this study to infer the genetic variation of A. aequalis by applying DNA sequencing technique whereas conserved gene 12S rRNA was used to infer phylogenetic relationships of Aethalops from Sundaland. Analyses of results were interpreted for within and among group variations. Discriminant Function Analysis (DFA) results showed little variation was detected in morphology of Malaysian A. aequalis. Characters of distance between lower canine and lower molar (CM1) and distance between lower incisor and lower molar (IM 1) were the two strongest characters to discriminate A. aequalis. Differences in CMI (indicating the length of lower jaw) showed a separation between Northeast Sarawak and Sabah (Northern part of Borneo) and Southwest Sarawak groups. Populations from lower elevation mountain at Southwest Sarawak have a longer lower jaw. Longer lower jaw can be related to feeding behavior of the fruit bat. Mt Mulu population showed significant differences in all characters against populations in Mt Penrissen, Mt Kinabalu, Mt Trus Madi and Mt Murud. Morphology differences were suggested to be influenced by the food resources in the environment. Phylogenetic analyses results showed that there was an interspecific genetic divergence in Aethalops, separated into two main groups which were A. alecto and A. aequalis. Using 12S rRNA, Kalimantan population was detected as the possible ancestral population of A. aequalis in Borneo. Highly significant genetic differences of A. aequalis between populations in Kalimantan and Malaysia Borneo suggested a possibility of two subspecies in Borneo. Both mitochondrial (12S rRNA and COI) and nuclear (Rag2) genes produced unresolved phylogenetic trees at population level. There was little genetic divergence and high gene flow detected among the observed populations in Sabah and Sarawak. However, each of the inferred genes were able to detect that there was a clear pattern in separation time of divergence between Southwest Sarawak and Northeast Sarawak and Sabah groups. It was predicted the population of Malaysian Borneo started from the Southwest Sarawak after diverging from Kalimantan population, then dispersed into Northern part of Borneo during the Pleistocene period. Molecular findings also showed incongruence results with morphological difference between Mt Mulu and other populations. Overall, A. aequalis was a single panmictic population. A single unit of ESUs with two potentially MUs was defined for proper management of conserving this species. Two possible MUs were suggested for populations from Mt Penrissen and Bario that acquire immediate conservation population in future studies with more adequate amount of samples representing each populations. Both of these populations were genetically different from other populations and also were suspected as an ancestral population for A. aequalis in Malaysia Borneo based from the preliminary findings. Therefore, it is very important to retain the ancestral haplotype from this population for genetic management purposes in Sarawak. However, more sufficient samples of A. aequalis are required to further verify the MUs in Sabah and Sarawak. Current findings on the abundance, morphology and genetic data of A. aequalis can be used as baseline information for the conservation and proper management on this species and habitats related to its survival.